“Significant Otherness” versus Othering in Marian Engel’s Bear - Hughes, Carys (Canada and Beyond: A Journal of Canadian Literary and Cultural Studies, 2023)
This article explores Marian Engel’s portrayal of what Animal Studies scholar Donna J. Haraway terms “significant otherness” (the simultaneous interconnection and mysterious difference between animal and human life/connections) and othering as a form of dismissal and a perpetuation of colonial hierarchies of gendered and racial power. I explore the overlaps of Engel’s othering of Indigenous characters in the novel and the racism present in speciesism, exposing why the character of the bear is more knowable to the protagonist than Lucy Leroy (Cree). I offer a decolonial reading of this seminal Canadian text, drawing on Engel’s desire to disrupt literary utilization of animals as images of nationalism and emblems of patriotic virtue, while simultaneously exposing the prevalence of entrenched gendered and racial hierarchical perceptions of Indigenous women and relationships to nature. In offering this reading, I hope to suggest that decolonial readings offer us the tools to integrate the ideals expressed in Haraway’s “significant otherness” reading of companion-animal relationships with decoloniality and the deconstruction of hierarchies of power as pioneered by Indigenous authors, artists, and activists. This generates hope.